Analisis Struktur Program Penguatan Bisnis Pemula bagi Wirausaha Pemuda Menggunakan Interpretive Structural Modeling - Rasdan, Rathoyo; ., Eriyatno; Affandi, M.Joko; ., Machfud (Jurnal Aplikasi Manajemen, 2013)
Unemployment increasing in Indonesia is currently a significant, especially unemployment of college graduates. Hence, the development of youth entrepreneurship can be an alternative solution. In the development progress of emerging entrepreneurship programs in a variety of higher education, but have not contributed significantly to job creation and unemployment reduction. In case the complex problems is necessary to study the structure of the program. The aim of this paper is to analyze the structure and key elements of strengthening start-up business program, which is one way of growing entrepreneurial youth.The interpretive structural modeling (ISM) methodology is used to envelop relationship among these elements. ISM approach begins with the identification of elements that correspond to the problem or issueuntil finally the distribution of elements and structures extraction models. The element of objective program have been identified base on their driving power and dependence power. The results shown the key element isto grow the start-up business services unit in college. To achieve these objectives have been element of possibly changes, namely entrepreneurship curriculum changing in college. Curriculum changes focused to characterbuilding and soft-skill, in addition the competence of graduates which are the objectives of national education.